A Human Lin− CD123+ CD127low Population Endowed with ILC Features and Migratory Capabilities Contributes to Immunopathological Hallmarks of Psoriasis - Mora-Velandia, Luz María; Castro-Escamilla, Octavio; Méndez, Andrés González; Aguilar-Flores, Cristina; Velázquez-Avila, Martha; Tussié-Luna, María Isabel; Téllez-Sosa, Juan; Maldonado-García, César; Jurado-Santacruz, Fermín; Ferat-Osorio, Eduardo; Martínez-Barnetche, Jesus; Pelayo, Rosana; et al. (Frontiers in Immunology, 2017)
Innate lymphoid cells (ILC) are members of a heterogeneous family with a lymphoid origin that mimics the T helper (Th) cytokine profile. ILC are involved in early effector cytokine-mediated responses during infections in peripheral tissues. ILC also play an important role in chronic skin inflammatory diseases, including psoriasis. Although classical ILC express CD127, it has been recently reported that the presence of non-classical CD127− ILC populations and an early ILC precursor (EILP) CD127low. ILC development has predominately been investigated in mouse models. However, in humans, different transcription factors have been described for ILC identification. NFIL3 (nuclear factor, IL-3 regulated) is crucial for ILC development in response to IL-7. CD123 (IL-3Rα) is usually used to exclude basophils during ILC identification, however, it is unknown if in response to IL-3, NFIL3 could be relevant to induce ILC features in Lin− CD123+ populations in addition, is also unknown whether peripheral blood (PB) population with ILC features may have skin-homing potential to participate in skin inflammatory chronic diseases. Here, we report a Lin− CD123+ CD127low CD7+ CLA+ population that share some phenotypic properties with basophils, but expresses several transcription factors for ILC commitment such as inhibitor of DNA binding 2 (Id2), NFIL3, promyelocytic leukemia zinc finger (PLZF), thymocyte selection-associated high-mobility group box protein (TOX), and T cell factor-1 (TCF-1). In addition, this population expresses different ILC markers: CD132, CD90, CD161, α4 integrin, c-Kit, CRTH2, AhR, and IL-23R. IL-3 prevents apoptosis and increases their NFIL3, TOX, and PLZF expression. In PB, the CD123+ CD127low population is predominantly a conspicuous population that expresses T-bet and RORγt. The Lin− CD123+ CD127low population in PB has a limited Th type cytokine expression and highly expresses IL-8. The Lin− CD123+ CD127low population expresses skin-homing receptors (cutaneous lymphocyte antigen and CXCR4) and transmigrates through endothelial cells in response to SDF-1. An equivalent Lin− CD123low population was identified in control skin, which shows a broader phenotypic diversity and cytokine production, including IL-22 and IL-17. Remarkably, the CD123low population in the lesion and non-lesion skin of psoriasis patients expresses IL-17 and IL-22. Our findings suggest the identification of an alternative Lin− CD123+ CD127low population with ILC features endowed with migratory capabilities that might contribute to immunopathological hallmarks of psoriasis.